PENGGUNAAN MEDIA ANIMASI PADA PEMBELAJARAN PAI UNTUK MENINGKATKAN MOTIVASI BELAJAR TUNAGRAHITA - Nilna Azizatus Shofiyyah; Asep Nursobah; Tarsono Tarsono (Psychosophia: Journal of Psychology, Religion, and Humanity, 2020)
The purpose of this study to explain the validation, implementation, factors, and effectiveness of animation media products in Islamic Religious Education Learning to improve learning motivation for children with developmental disabilities in SLB Angkasa Lanud Sulaiman. This type of research is a qualitative case study approach, taking place in SLB Angkasa Lanud Sulaiman. The results showed: 1) The validation of animated media products in Islamic learning PAI material was 94.1 and 91.4 If converted into an evaluation table the results of expert trials included in the "very good" criteria. 2) Implementation of PAI learning using animation media follows the steps made in the learning implementation plan. 3) Supporting factors that influence the learning of PAI using animation media are the ease of the animation media themselves to be used and the display of animated media which makes intellectual children easily understand the PAI material delivered, such as the pillars of Islamic principles. The inhibiting factor is the cost to access the animation media. 4) The level of success is shown in the value of mentally disabled students through reports on learning outcomes for mentally retarded students who get an average value of 80 of minimal completeness criteria of 75.